2010
DOI: 10.1016/j.biopsych.2010.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Early Processing of Threat Cues in Posttraumatic Stress Disorder—Evidence for a Cortical Vigilance-Avoidance Reaction

Abstract: The increased early activity in the right prefrontal cortex most likely represents an enhanced alarm response or the fear network toward aversive stimuli in PTSD, whereas the subsequent decreased activation in right parieto-occipital areas in response to aversive pictures seems to reflect the tendency to disengage from emotional content. This finding is consistent with the hypothesis of a vigilance-avoidance reaction pattern to threat in anxiety disorders and helps to reconcile contradicting results of over- a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
50
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 45 publications
9
50
2
Order By: Relevance
“…More intense evaluation of emotional pictures in PTSD has also been reported by Adenauer et al (2010) and Hayes et al (2011). The general finding that emotional significance modulates DF is in line with previous research, but the reported patterns vary.…”
Section: Discussionsupporting
confidence: 85%
“…More intense evaluation of emotional pictures in PTSD has also been reported by Adenauer et al (2010) and Hayes et al (2011). The general finding that emotional significance modulates DF is in line with previous research, but the reported patterns vary.…”
Section: Discussionsupporting
confidence: 85%
“…It may be the case that the high intensity of threat associated with traumatic events causes more minor patterns of attentional avoidance to propagate to other cognitive systems and manifest more robustly in the form of dissociation. Evidence from neuroimaging research in PTSD patients lends support this possibility of a biphasic process of initial attentional vigilance toward threats and later threat avoidance (Adenauer et al 2010).…”
Section: Discussionmentioning
confidence: 96%
“…They hypothesized that the early prefrontal increased cortex response represents the enhanced alarm response and the secondary decreased activation of the parieto-occipital areas represented the emotional disengagement common in PTSD patients. 76 …”
Section: Narrative Exposure Therapy (Net)- Innovative Ideas To Treat mentioning
confidence: 99%